Optimisation in daily practice – it's more than just radiation dose. Issue 1 (9th March 2020) - Krupinski, Elizabeth A.
Abstract : On this editorial, the importance of optimisation of diagnostic imaging and radiation therapy in terms of diagnostic and therapeutic tests and treatments, education and service provision are discussed.